Psychological Dynamics of Increasing Guilt Feelings in Prisoners in Child Violance Convicts at the Class IIA Madiun Youth Prisons - Putri, Risqianita Widodo; Aulia, Qisthina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Child abuse cases inflict profound trauma on the victims and often engender a complex sense of guilt in the perpetrators, stemming from the multifaceted repercussions they face post-incarceration. This study aims to conduct a qualitative examination of the guilty feelings experienced by inmates convicted of crimes against children at the Class IIA Madiun Youth Correctional Facility. It is hypothesized that a pronounced and constructive sense of guilt is positively correlated with enhanced self-reform among inmates. A narrative qualitative methodology was employed, utilizing in-depth interviews, participatory observation, and documentary analysis. The research subjects comprised inmates serving minimum sentences of five years for sexual offenses against children. The findings indicate that inmate guilt manifests in two primary dimensions: guilt directed inward (self-reproach) and guilt directed outward (toward the victim). This guilt significantly influences affective, cognitive, behavioral, and motivational domains, catalyzing a process of critical self-reflection that is facilitated by the institution's psychologically-oriented rehabilitation programs. The emergence of this guilt is attributed to several factors, including normative understanding, personal accountability, social expectations, and emotional responsiveness. This research provides a deeper conceptual understanding of how eliciting guilt in offenders can serve as a pivotal mechanism for positive personal development and behavioral reform within the penal system.Kasus kekerasan pada anak tak hanya meninggalkan trauma terhadap anak itu sendiri, melainkan juga meninggalkan rasa bersalah bagi narapidana karena berbagai dampak yang diterimanya pasca kekerasan. Penelitian ini bertujuan untuk mengkaji rasa bersalah (guilty feeling) yang dialami oleh narapidana kasus perlindungan anak di Lapas Pemuda Kelas IIA Madiun. Hipotesis menyatakan bahwa narapidana dengan rasa bersalah yang tinggi dan positif memunculkan perbaikan diri yang lebih baik. Penelitian menggunakan metode naratif kualitatif dengan wawancara mendalam, observasi, dan dokumentasi. Subjek penelitian terdiri dari narapidana yang terlibat dalam kasus kejahatan seksual terhadap anak dengan minimal hukuman penjara 5 tahun. Hasil penelitian menunjukkan bahwa rasa bersalah pada narapidana muncul dalam dua bentuk: rasa bersalah terhadap diri sendiri dan korban. Rasa bersalah ini mempengaruhi dimensi afektif, kognitif, perilaku, dan motivasi, serta mendorong narapidana untuk merefleksikan tindakan mereka melalui pembinaan berbasis psikologis di Lapas. Faktor rasa bersalah ini muncul akibat pemahaman norma, perasaan tanggung jawab, ekspektasi sosial, dan respons emosional. Penelitian ini memberikan pemahaman lebih mendalam tentang memunculkan rasa bersalah pada narapidana yang kemudian berdampak positif terhadap pengembangan dan perbaikan diri.